Найвидатніші постаті національного ботанічного саду ім. М.М. Гришка НАН України – М.М. Гришко, Л.І. Рубцов, С.С. Харкевич, Є.М. Кондратюк, А.М. Гродзінський - Cherevchenko, T.M.; Chuvikina, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
The data about the outstanding scientists, worked at M.M. Gryshko National Botanical Gardens of the NAS of Uk raine, – Academicians M.M. Gryshko and A.M. Gro dzinsky, corresponding member E.M. Kondra tyuk, Doktors of biological sciences L.I. Rubtsov and S.S. Kharkevych are given.